PENGARUH KEBISINGAN, UMUR, MASA KERJA, LAMA PAPARAN DAN PENGGUNAAN ALAT PELINDUNG TELINGA PADA TENAGA KERJA DI PERUSAHAAN KABEL OTOMOTIF - Abjasiqo, Mahesi Yustika; Winarko, Winarko; Sari, Ernita (Ruwa Jurai: Jurnal Kesehatan Lingkungan, 2020)
PT. Indowire Prima Industrindo is a company that manufactures copper automotive cables. In the operational process, it causes noise to reach 79-103 dBA. The study was conducted to obtain an overview of risk factors in the production section, namely age, years of service, duration of exposure, and use of PPE.The study used an observational research design with a descriptive study method, with a total sample of 62 people chooses randomly. Data collected through interviews, observations, and measurements.The results of research at PT. Indowire found that only 21% of qualified workplace noise. Most workers (93.5%) are older than 40 years old and have a working period of more than 10 years of 22.6%. All workers in the production section get noise exposure for 7 hours/day, and 21% do not use PPE. This study of noise indicates a high risk for hearing loss.There is a need for technical control efforts, the implementation of a work rotation system, training on APT, as well as providing strict supervision and policies for workers who do not use APT in noisy workplacesÂ